2016
DOI: 10.1111/jbi.12689
|View full text |Cite
|
Sign up to set email alerts
|

Testing dispersal limits in the sea: range‐wide phylogeography of the pronghorn spiny lobster Panulirus penicillatus

Abstract: Aim To resolve phylogeographical partitions in the pronghorn spiny lobster, Panulirus penicillatus, which has a nine-month pelagic larval phase and the broadest distribution among spiny lobsters. With samples from the Red Sea to the East Pacific, we test genetic partitions across two-thirds of the planet, in a species with one of the longest pelagic phases.Location Red Sea, Indian and Pacific Oceans.Methods A fragment of the mtDNA cytochrome c oxidase subunit I gene (COI) was resolved in 774 individuals from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 79 publications
1
28
0
Order By: Relevance
“…The pronghorn spiny lobster, Panulirus penicillatus, with a 9-mo pelagic larval duration and a distribution across the entire tropical Indo-Pacific, illustrates genetic diversification at both ends of its range. Iacchei et al (21) found fixed differences in mtDNA of East Pacific and Red Sea populations (Φ ST = 0.74), corroborated by morphological differentiation in the East Pacific (58). Speciation in peripheral provinces is apparent in Thalassoma wrasses (59), Anampses wrasses (60), Acanthurus surgeonfishes (55), Mulloidichthys goatfishes (19), and Montastraea corals (61).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The pronghorn spiny lobster, Panulirus penicillatus, with a 9-mo pelagic larval duration and a distribution across the entire tropical Indo-Pacific, illustrates genetic diversification at both ends of its range. Iacchei et al (21) found fixed differences in mtDNA of East Pacific and Red Sea populations (Φ ST = 0.74), corroborated by morphological differentiation in the East Pacific (58). Speciation in peripheral provinces is apparent in Thalassoma wrasses (59), Anampses wrasses (60), Acanthurus surgeonfishes (55), Mulloidichthys goatfishes (19), and Montastraea corals (61).…”
mentioning
confidence: 87%
“…The East Pacific Barrier (EPB) limits the distribution of tropical species (62), with few taxa able to maintain population connectivity across the EPB, as evidenced by the lobster P. penicillatus (21), and the coral Porites lobata (63,64). However, some fishes (65) and the echinoderm Echinothrix diadema (66) have low or insignificant Φ ST values across the EPB.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Where individual species are distributed across two or more biogeographic provinces, shifts in genotype frequencies often align with biogeographic boundaries, providing intraspecific concordance between biogeography and phylogeography. Recent examples among marine taxa include sea snails (Brante, Fernández, & Viard, ); clams (DeBoer et al., ); Indo‐Pacific goatfish, Mulloidichthys flavolineatus (Fernandez‐Silva et al, ); spiny lobster, Panulirus penicillatus (Iacchei, Gaither, Bowen, & Toonen, ); barnacles (Ewers‐Saucedo et al, ); and seaweeds in the southeast Pacific (Guillemin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…() examine a widespread goatfish species and find that phylogeographical breaks are congruent with existing boundaries of biogeographical provinces, and that these peripheral biogeographical provinces may represent evolutionary incubators for reef fishes ( sensu Bowen et al., ). Broadening the taxonomic scope, Iacchei, Gaither, Bowen and Toonen () find similar concordance of phylogeographical and biogeographical barriers in the spiny lobster (also see Bowen et al., ). Higher‐resolution studies such as Priest et al.…”
Section: Editorialmentioning
confidence: 99%